Use of Negative Pressure Wound Therapy Systems after Radical Vulvectomy for Advanced Vulvar Cancer. (20th October 2020) - Quercia, Vittorio; Saccone, Gabriele; Raffone, Antonio; Travaglino, Antonio; Favale, Mariano; D'Alessandro, Pietro; Arduino, Bruno; Carbone, Ilma Floriana; Insabato, Luigi; Ribuffo, Diego; Zullo, Fulvio
Abstract: A retrospective cohort study was performed to evaluate the efficacy of negative pressure wound therapy in improving vulvectomy healing. Women who underwent radical vulvectomy with complete inguinofemoral lymphadenectomy for advanced vulvar cancer were divided into two groups according to immediate postoperative care: patients treated with negative pressure wound therapy using the device applied on the site of the wound (including vulva and inguinal region), and patients receiving conventional care. 18 patients were included in the study. 7 (38.9%) women were treated with negative pressure wound therapy immediately after the surgery and were included in the intervention group, and 11 (61.1%) patients were included in the control group. Women who received negative pressure wound therapy had significantly lower length of stay in the hospital (14.2 ± 4.7 versus 17.1 ± 6.1 days, mean difference −6.90 days, 95% confidence interval −11.91 to −1.89), and significantly lower length for wound healing (−31.90 days, 95% confidence interval −43.48 to −20.32). In conclusion, the utilization of the negative wound pressure therapy may contribute to reduce hospitalization after radical vulvectomy for vulvar cancer. Large and well-designed randomized trials with cost effectiveness analyses are needed to confirm these findings.